Theoretical Foundations of the First Purchase in Marketing - Hristov, Alexander (Research Papers, 2021)
Consumer decision making as an important process in marketing sphere has been discussed in detail, but so far researchers as a rule have not focused the attention on how the purchase happens for the very first time. The current text is an attempt to develop the foundations and to make a conceptual framework of the first purchase in marketing and to outline its significance for current or future consumption, especially for the fast-moving consumer goods (FMCG). Together with a review of the extent to which the first purchase is considered and interpreted in the academic tradition in the field (and in practice), an attempt has been made to outline it as a phenomenon, since it can have significant benefits for better understanding consumer behavior and the further improvement of marketing communications.With this regard, it can be assumed that the first purchase is the initial step of acquiring consumer experience, which determines whether the product will continue to be purchased or not. Of course, all this is largely valid for the b2c (business to consumer) markets, for the products for individual and household consumption, and for the b2b (business to business) ones the particularities may differ significantly and need to be a subject of additional research efforts.